2022
DOI: 10.1002/edn3.275
|View full text |Cite
|
Sign up to set email alerts
|

Development of species‐specific multiplex real‐time PCR assays for tracing the small pelagic fishes of North Pacific with environmental DNA

Abstract: The ocean covers about 70% of the Earth's surface, and marine ecosystems are an important food supply for the world population.According to the report by the Food and Agriculture Organization (FAO, 2018) of the United Nations, about 20.5 kg of marine products (63% from the ocean) is consumed per capita per year. Among marine products, about 73% are wild fish catch while aquaculture

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Extracted genomic DNA was used, instead of a gBlock, to establish the LOD and LOQ. As in some of the other recent studies [marine pelagic fish species in Wong et al (2022) and Esox lucius in Karlsson et al (2022)] which used genomic DNA for the LOD and LOQ calculations, we assumed no interference during PCR from the rest of the species’ genome, other genetic material or potential co‐extracted inhibitory compounds. The mesocosm experiments, as well as sites where A. cryptocallus had been captured previously and which served as positive controls, allowed further validation of the methodology.…”
Section: Discussionmentioning
confidence: 99%
“…Extracted genomic DNA was used, instead of a gBlock, to establish the LOD and LOQ. As in some of the other recent studies [marine pelagic fish species in Wong et al (2022) and Esox lucius in Karlsson et al (2022)] which used genomic DNA for the LOD and LOQ calculations, we assumed no interference during PCR from the rest of the species’ genome, other genetic material or potential co‐extracted inhibitory compounds. The mesocosm experiments, as well as sites where A. cryptocallus had been captured previously and which served as positive controls, allowed further validation of the methodology.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that data for benthic species should be the most accurate due to their sedentary nature. On the other hand, while this method still presents challenges in accurately quantifying species abundance (Wong et al, 2022), it proves valuable for detecting a diverse set of species in our study area, including cryptobenthic species. Aglieri et al (2020) showed that eDNA monitoring may go beyond the identification of taxonomic entities and be applied to ecological studies of functional diversity, providing more robust results than sampling with fishing nets or baited underwater video.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative multiplex PCR (e.g. Wong et al, 2022) can measure eDNA for several target species, small species, and even cryptic species, but is limited for quantitative assessment (e.g., Shelton et al, 2023). Diversity, evenness and dominance can also be influenced by other factors such as food availability or contamination, independently or synergistically with deoxygenation (Rozenzweig and Abramsky, 1993;Levin and Gage, 1998;Pilo et al, 2015).…”
Section: Ecosystem Indicatorsmentioning
confidence: 99%